Analisis Peta Wilayah Kecamatan Pangean Berbasis Web Menggunakan Sistem Informasi Geografis (GIS) - Fitria Arum Damayanti; Rido Andri Wibowo; Lucky Pratiwi; Laila Pasrah (Yasin Publisher (Yayasan Amal Sosial Islami Nahdliyin), 2026)
The rapid development of information technology has encouraged the utilization of Geographic Information Systems (GIS) as an effective and accessible tool for managing and presenting spatial data. Pangean District, as one of the administrative regions, requires accurate and informative map visualization to support regional planning and provide geographic information services to the public. This study aims to analyze and present a web-based regional map of Pangean District using Geographic Information System (GIS) technology. The research method includes the collection of spatial and non-spatial data, data processing using GIS software, and the presentation of results in the form of digital maps that can be accessed through a web platform. The analysis was conducted based on the generated spatial information to provide a visual and interactive representation of the location and distribution of the district's geographical features. The results indicate that the implementation of a web-based GIS facilitates access to geospatial information, enhances the effectiveness of regional data presentation, and helps users better understand the geographical characteristics of Pangean District. Therefore, the developed web-based regional map is expected to serve as a valuable source of information for the public and relevant stakeholders in supporting decision-making and regional planning.